2010
DOI: 10.1364/josab.27.001664
|View full text |Cite
|
Sign up to set email alerts
|

Optical precursors in the singular and weak dispersion limits

Abstract: The description of the precursor fields in a single-resonance Lorentz model dielectric is considered in the singular and weak dispersion limits. The singular dispersion limit is obtained as the damping approaches zero and the material dispersion becomes increasingly concentrated about the resonance frequency. The algebraic peak amplitude decay of the Brillouin precursor with propagation distance z Ͼ 0 then changes from a z −1/2 to a z −1/3 behavior. The weak dispersion limit is obtained as the material density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…More than a century after their discovery, these transients, currently named Sommerfeld and Brillouin precursors, continue to raise considerable interest, due in particular to their sub-exponential attenuation with the propagation distance. An abundant bibliography on the subject is given in Ref [5] and more recent related studies are reported in Refs [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…More than a century after their discovery, these transients, currently named Sommerfeld and Brillouin precursors, continue to raise considerable interest, due in particular to their sub-exponential attenuation with the propagation distance. An abundant bibliography on the subject is given in Ref [5] and more recent related studies are reported in Refs [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…An abundant bibliography on forerunners can be found in [16]. For most recent studies related to the forerunners in the sense of Sommerfeld and Brillouin, see [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…OCIS codes: 260.2030, 320.5550, 320.2250. In a recent paper [1], Oughstun et al revisit the classical problem of the propagation of a step modulated pulse in a Lorentz model medium. They specifically consider the case where the absorption line is narrow (singular limit) and the one where the refractive index of the medium keeps very close to unity at every frequency (weak dispersion limit).…”
mentioning
confidence: 99%
“…Although it abundantly refers to the theoretical results obtained by the asymptotic method, the study reported in [1] is mainly numerical. All the simulations are made for ω 0 = 3.9 × 10 14 rad/s [2] and ω c = 3.0 × 10 14 rad/s in a normal dispersion region.…”
mentioning
confidence: 99%
See 1 more Smart Citation